THE EFFECT OF BLENDED LEARNING USING SCHOOLOGY TOWARD STUDENT LEARNING OUTCOMES ON WORK AND ENERGY TOPIC IN SMAN 1 PERBAUNGAN - Lestari Lumban Gaol; Makmur Sirait (LPPM Universitas Negeri Medan, 2019)
This research aims to determine the effect of blended learning using schoology toward student learning outcomes on work and energy topic at grade X MIA in SMAN 1 Perbaungan. This type of research is quasi-experimental. The population in this research were all students of class X MIA in SMAN 1 Perbaungan which consisted of 4 classes. The sample selection was purposive sampling where class X MIA 1 as the experimental class and X MIA 2 as the control class. The results of the average value of the experimental class pretest 46.97 and the control class 45.9 both samples were normally distributed and homogeneous. Based on the two tail t-test analysis obtained the initial ability of the two samples is the same. After that, different treatments were given in both classes and posttest was performed, the results of the experimental class average score was 78.67 and the control class was 63.67. One tail t-test analysis was obtained that there was an effect of blended learning using schoology toward student learning outcomes on work and energy topic at grade X MIA in SMAN 1 Perbaungan.